Elevated transferrin saturation in individuals with alcohol use disorder: Association with HFE polymorphism and alcohol withdrawal severity. (5th February 2022) - Kroll, Danielle S.; McPherson, Katherine L.; Manza, Peter; Schwandt, Melanie L.; Shen, Pei‐Hong; Goldman, David; Diazgranados, Nancy; Wang, Gene‐Jack; Wiers, Corinde E.; Volkow, Nora D.
Abstract: Iron loading has been consistently reported in those with alcohol use disorder (AUD), but its effect on the clinical course of the disease is not yet fully understood. Here, we conducted a cohort study to examine whether peripheral iron measures, genetic variation in HFE rs1799945 and their interaction differed between 594 inpatient participants with alcohol use disorder (AUD) undergoing detoxification and 472 healthy controls (HC). We also assessed whether HFE rs1799945 was associated with elevated peripheral iron and can serve as a predictor of withdrawal severity. AUD patients showed significantly higher serum transferrin saturation than HC. Within the AUD group, transferrin saturation significantly predicted withdrawal symptoms (CIWA‐Ar) and cumulative dose of benzodiazepine treatment during the first week of detoxification, which is an indicator of withdrawal severity. HFE rs1799945 minor allele carriers showed elevated transferrin saturation compared to non‐carriers, both in AUD and healthy controls. Exploratory analyses indicated that, within the AUD cohort, HFE rs1799945 predicted CIWA withdrawal scores, and this relationship was significantly mediated by transferrin saturation. We provide evidence that serum transferrin saturation predicts alcohol withdrawal severity in AUD. Moreover, our findings replicated previous studies on elevated serum transferrin saturation in AUD and an involvement of HFE rs1799945 in serum transferrin saturation levels in both AUD and healthy controls. Future studies may use transferrin saturation measures as predictors for treatment or potentially treat iron overload to ameliorate withdrawal symptoms. Abstract : We found elevated peripheral iron measures including transferrin saturation in individuals with alcohol use disorder (AUD) compared to non‐dependent healthy controls. Within the AUD group, transferrin saturation covaried with alcohol withdrawal severity and with benzodiazepine use during the first week of detoxification, and genetic variation in HFE rs1799945 covaried with transferrin saturation and with withdrawal severity. We provide evidence for elevated iron loading in AUD that may be clinically relevant during detoxification.